The Effect of Using Retelling Strategy In Reading Comprehension At First Semester English Education Muhammadiyah University of Bengkulu - Arjun pauzi; Fetriani (Teaching English and Language Learning English Journal, 2024)
This research focused on the effect of using the Retell Strategy on the reading comprehension of students in the first semester of English education at Muhammadiyah University of Bengkulu. The problem in this research is that the majority of students have low reading comprehension. Crucial problems that affect students' reading comprehension are: students' reading comprehension is low, English vocabulary is low, students do not have much interest in reading text comprehension. This research aims to describe students' knowledge in reading comprehension and students' problems in the learning process using Retelling Strategy in students in the first semester of English education at Muhammadiyah University of Bengkulu. This research was carried out as experimental research, the population of this study was first semester English students at Muhammadiyah University of Bengkulu. The total population consists of 25 students. Then, the sample of this research was divided into two classes, first, the experimental class and second, the control class, consisting of 25 students. To collect data, researchers use tests to measure. To analyze the data, researchers used the t-test formulation. Based on the research results, researchers found that the results of the experimental class were higher than the control class. The average score for the experimental and control classes in the pre-test was (32.00> 31.20), the average score for the experimental class and control class in the post-test was (48.40> 40.40). The effect of using the Retell Strategy on students' reading comprehension was 4.421> 2.063 with to higher than tt. That means Ha is accepted and H0 is rejected. So, it is concluded that there is a significant effect of using the Retell Strategy on the Reading Comprehension of students in the first semester of English education at Muhammadiyah University of Bengkulu. Keywords: Reading Comprehension, Retelling Strategies